Integrating Patient Perspectives and Process Observation to Evaluate Inpatient Food Service Quality: Evidence from an Indonesian Regional Hospital - Nurfaidah; Nurul Chaerunnisa, Novia; Alam, Nur; Asikin, Abdul Malik (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction: Food service quality is an essential component of hospital nutrition services because it influences patients' food acceptance, nutritional intake, and satisfaction during hospitalization. Previous evaluations have primarily relied on patient satisfaction surveys, whereas studies integrating patient perceptions with direct observations of the food distribution process remain limited, particularly in regional public hospitals. This study aimed to describe inpatient food service quality at Syekh Yusuf Regional General Hospital, Gowa Regency, Indonesia, based on patients' perceptions and observations of the meal distribution process. Methods: A descriptive observational study with a cross-sectional design was conducted among 41 inpatients receiving regular diets. Participants were selected using purposive sampling. Data were collected using a patient satisfaction questionnaire and a structured observation checklist based on the Indonesian Hospital Nutrition Service Guidelines (PGRS). The evaluated dimensions included food taste, meal temperature, food texture, menu variety, cleanliness of eating utensils, staff attitude, timeliness of meal distribution, and overall patient satisfaction. Data were analyzed descriptively using frequencies and percentages. Results: All observed food distribution indicators complied with the hospital's operational standards (8/8 indicators). Patients generally reported positive evaluations across the assessed food service dimensions. Food texture received the highest positive evaluation (97.6%), followed by food taste (68.3%), staff attitude (68.3%), and timeliness of meal distribution (68.3%). Meal temperature (56.1%) and menu variety (53.7%) received comparatively lower ratings. Overall, 61.0% of respondents were very satisfied and 39.0% were satisfied with the hospital food service. Conclusion: Integrating patient perceptions with direct observations provides a comprehensive description of inpatient food service quality. Meal temperature and menu variety may represent priorities for continuous quality improvement, while maintaining the favorable performance observed for utensil cleanliness, staff professionalism, and timely meal distribution.